Dropout and compliance to physical exercise in menopausal osteopenic women: the European “happy bones” project - Grazioli, Elisa; Cerulli, Claudia; Tranchita, Eliana; Moretti, Elisa; Mauri, Caterina; Broccatelli, Marianna; De Bellonia, Simona; Abalașei, Beatrice-Aurelia; Dumitru, Iulian-Marius; Moraru, Cristina-Elena; Iacob, Radu-Mihai; Blancafort-Alias, Sergi; et al. (Frontiers in Sports and Active Living, 2023)
Introduction Decline in muscle mass and bone density seem to be two of the most disabling side effects of menopause that negatively affect women's quality of life. Promoting physical activity protocols in the workplace can represent a focal point in the prevention and management of several diseases. The study aims to evaluate the compliance and drop-out of menopausal osteopenic women engaged in combined training performed inside and outside the workplace. Strength and balance were analyzed to evaluate the effect of this protocol on osteoporosis prevention and the risk of falling. Methods 73 menopausal women were enrolled in 5 European countries. They performed 72 lessons of a combined training proposed in the working place (IW) or sport center (SC). Results Out of the total 39 women enrolled in the IW, 12.8% had to leave the program, while out of the 34 women enrolled in SC, 41.2% did not complete the training. According to the compliance results, 47% of women that completed the trained IW and 85% in the SC recorded high compliance (p = 0.019). Moreover, the strength of the lower limbs (p < 0.001) and static balance (p = 0.001) significantly improved in the whole group. Discussion In conclusion, proposing well-structured training in the workplace for menopausal women seems to reduce drop-out. Strength and balance results suggest its positive impact on bone health and risk of falls, despite where it is performed.